Peningkatan Pembelajaran Tematik Terpadu dengan Model Problem Based Learning di Kelas IV Sekolah Dasar - Juliadi, Oni; Fachrudin, Farida; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims to improve the rade students’ integrated thematiclearning process by using the problem based learning model in class IV. This type of research is Classroom Action Research, using qualitative and quantitative approaches. The subjects were the teacher and the grade students in class IV. The result of the research revealedthat from the first cycle to the secound one. The score of the lesson plan improved from 86,11% to 97,22%. the teacher’s activities improved from 81,24% to 94,64%, thestudents activities improved from 78,56% to 92,86%. and the students learning achievementimproved from 2,89 to 3.48.